Burials in the territory of the Vilnius Kalnų (Hill) Park - Kontrimas, Darius (Archaeologia Lituana, 2025)
In 1989 Daiva Misiukaitė (Daiva Luchtanienė) conducted exploratory archaeological research in the Vilnius Kalnų (Hill) park – teritory in which, it is believed, one of the main medieval castles of Vilnius – the Crooked Castle was located. Graves were discovered in three places: in the northwestern part of the Dainų Valley, near the current parking lot, on the The Hill of Gediminas’ Grave and in the southern part of Altana hill. In the latter place, archaeological research was carried out again in 2021. In the first two burial sites, no finds allowing dating of the graves were found - the chronology remained unclear. In the third place, finds were found in only three graves - the graves were tentatively dated to the 17th century and associated with the events of the 1655-1661 when Vilnius was occupied for the first time by Russian army. In 1989 anthropological examination of the discovered graves was not carried out, but all osteological material was kept at the Faculty of Medicine of Vilnius University until now. It was decided to conduct these studies in 2021. 14C dating of samples taken from 14 graves was also carried out. The purpose of this article is to clarify the chronology of graves by using statistical modeling, to assess the general archaeological and historical context, to publish the results of anthropological research and laboratory dating.